Factores determinantes de la calidad del servicio en la agencia central del Banco de Crédito del Perú (BCP), del distrito de Tarapoto. Año 2014 - Castro Saavedra, Jhoslly Joao (2015)
This research is based on the requirement of QoS in financial institutions since there are many aspects that we consider to qualify good service, currently there are multiple factors of competitiveness and customer satisfaction, which is why This research was conducted to identify the determinants of service quality in the Central Agency Credit Bank of Peru in the city of Tarapoto. It has been prepared in the nonexperimental cross-sectional design and research method that was used in this project was inductive. This research has been prepared following the methodological guidelines of the SERVQUAL, where the operating aspect relates to the performance of the service, the physical aspect has to do with the appearance of facilities, new technologies include virtual media like the Internet and telephone banking, and human aspect comprises the attitudes and skills of employees in the service. The data processing was performed qualitative technically evaluating the events found by describing tables and graphs which were considered important and necessary for the information activities; were grouped and the data we obtained in the field work was structured, tools and programs for data processing defined, opting accurate survey taken towards exclusive customers, The results showed that operational processes have the highest value and is the greatest influence on the quality of service. This responds to the need for service because customers usually thought of as quality of service that related to performance in banking transactions, such as bank schedules, explanations, the waiting time in the queue, profitability, etc., subtracting some importance to the physical aspect of the organization, and the visual appearance of the employees, because what really matters to them are other most crucial aspects for them.